Dietary profile and changes in lipid, cortisol and testosterone levels in elite amateur cyclists during the 2010 GiroBio road cycling stage race: an innovative health promotion event - Simonetto, L.; Fiorella, P.; Broccardo, D.; Impellizzeri, F. M.; Trenti, T.; Mattei, R.; Ferrara, G.; Giorgi, A.; Bonifazi, M. (Medicina dello Sport, 2013)
SUMMARY The aim of the study was to evaluate a sample of elite amateur road cyclists during the 2010 GiroBio (amateur Giro d'Italia). The race format was a 10-day cycling stage race held according to innovative management rules with a special focus on health prevention. Dietary caloric intake and energy expenditure were measured during the event in 21 road cyclists. Changes in lipid profile, cortisol, total and free testosterone were measured from blood samples taken before, during, and at the end of the race. The blood parameters were then compared against the riders' placing at the end of the race. The values of macronutrients and principal micronutrients are reported. Total energy was estimated by calculating the individual external mechanical work for each stage. The riders' body mass was found to change during the race in relation to daily energy expenditure; however, the final value was substantially similar to the baseline value. The daily energy intake (kcal (kg)) during the race was inversely correlated to the final placing in classification, i.e., a better placing corresponded to a higher intake of energy as measured in kcal/kg. During the race, total cholesterol, low-density lipoprotein cholesterol and triglyceride levels decreased, whereas high-density lipoprotein cholesterol increased over baseline values. A decrease in cortisol and free testosterone concentrations was noted at the end of the race, whereas testosterone remained unchanged. Baseline testosterone concentration correlated with the final placing in classification, i.e., a higher placing corresponded to lower testosterone baseline levels. The data suggest that maintenance of the energy balance is a crucial factor in performance during a cycling stage race. The observed changes in lipid and hormone concentrations could reflect adaptation mechanisms that help to maintain energy balance during a road cycling race.